2016
DOI: 10.1038/srep24922
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs harboring miRNA seed regions are enriched in prostate cancer exosomes

Abstract: Long non-coding RNAs (lncRNAs) form the largest transcript class in the human transcriptome. These lncRNA are expressed not only in the cells, but they are also present in the cell-derived extracellular vesicles such as exosomes. The function of these lncRNAs in cancer biology is not entirely clear, but they appear to be modulators of gene expression. In this study, we characterize the expression of lncRNAs in several prostate cancer exosomes and their parental cell lines. We show that certain lncRNAs are enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 44 publications
0
130
0
Order By: Relevance
“…SChLAP1 may therefore be a favorable biomarker for assessing various treatment options for patients with PCa. Another lncRNA, SAP30L-AS1, was one of the lncRNAs existing in exosomes isolated from four PCa cell lines [18]. The current study is the first study to investigate the expression of SAP30L-AS1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SChLAP1 may therefore be a favorable biomarker for assessing various treatment options for patients with PCa. Another lncRNA, SAP30L-AS1, was one of the lncRNAs existing in exosomes isolated from four PCa cell lines [18]. The current study is the first study to investigate the expression of SAP30L-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…So far, every cell that has been studied secretes exosomes. Previous studies have demonstrated that tumor-derived exosomes had higher content of miRNA and lncRNA [18, 32, 48, 49]. It was the first of these studies that indicated that exosomes could transport mRNA, miRNA and angiogenic proteins leading to tumor growth and providing blood-based diagnostic information [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In exosomes and ectosomes, miRNAs are typically enriched. One of the reasons is that these vesicles also contain larger RNAs, especially lncRNAs and circular RNAs (circRNAs) that act as miRNA "sponges" by binding a high amount of miRNA molecules [9,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The development of future isolation techniques for prostasomes found in biological fluids will let to get better insight in the identification and analysis of the protein, lipid and nucleic acids content of them and the potential utility for the diagnosis and prognosis of prostate cancer. Exosomal miRNAs in prostate cancer miRNAs are expressed not only in cells and present in biological fluids, but can be found also in cell-derived extracellular vesicles such as exosomes [51]. In fact, RNA sequencing analysis of plasma-derived exosomes revealed that miRNAs are the most abundant exosomal RNA species [52].…”
Section: Exosomes and Prostasomesmentioning
confidence: 99%